2017
DOI: 10.2217/pgs-2016-0183
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 Pharmacogenetic and Oxycodone Pharmacokinetic Association Study in Pediatric Surgical Patients

Abstract: CYP2D6 phenotypes explain metabolism of oxycodone in children, and oxymorphone exposure is higher in CYP2D6 EM phenotype. Further studies are needed to predict the occurrence of adverse event and tailor oxycodone dose for a specific CYP2D6 phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…All C max values of oxycodone were below 10 ng/mL, C max of oxymorphone was below 0.3 ng/mL, and t ½ of oxycodone was 2.7 h. Patients with a more active CYP2D6 phenotype (n = 13 or 16) had higher concentrations of oxymorphone in comparison with phenotypes with less activity of CYP2D6 (n = 17 or 14). However, oxymorphone C max and oxymorphone:oxycodone ratios were low, between 0.01 and 0.05, in all three phenotypes (PMs, IMs and NMs) [89].…”
Section: Oxycodone In Childrenmentioning
confidence: 85%
See 1 more Smart Citation
“…All C max values of oxycodone were below 10 ng/mL, C max of oxymorphone was below 0.3 ng/mL, and t ½ of oxycodone was 2.7 h. Patients with a more active CYP2D6 phenotype (n = 13 or 16) had higher concentrations of oxymorphone in comparison with phenotypes with less activity of CYP2D6 (n = 17 or 14). However, oxymorphone C max and oxymorphone:oxycodone ratios were low, between 0.01 and 0.05, in all three phenotypes (PMs, IMs and NMs) [89].…”
Section: Oxycodone In Childrenmentioning
confidence: 85%
“…Balyan et al [89] evaluated the impact of genetic polymorphism of CYP2D6 on the PK of oxycodone in 30 children aged 2-17 years receiving oxycodone 0.07-0.1 mg/kg orally in the early postoperative period. Consistent with earlier data, delayed absorption was observed in some subjects, with a T max of 12 h indicating that absorption of swallowed oxycodone is erratic early after surgery and anaesthesia.…”
Section: Oxycodone In Childrenmentioning
confidence: 99%
“…Although differences in the pharmacokinetics of oxycodone based on CYP2D6 metabolizer status are evident, there are contradictory data regarding the differences in analgesia or toxicity (reviewed in [ 63 , 64 ]). There is one report of the impact of CYP2D6 metabolizer status on oxycodone pharmacokinetics in adolescents, where results were consistent with adult pharmacokinetic studies [ 18 ]. Although this study confirmed that CYP2D6 normal metabolizers had higher oxymorphone exposure than poor or intermediate metabolizers, more data are needed to support the oxycodone– CYP interaction before genotype-guided oxycodone dosing is clinically implemented for children.…”
Section: Resultsmentioning
confidence: 53%
“…One study of postsurgical paediatric patients found greater levels of oxymorphone in children who were RM or EM phenotypes compared with PM and IM phenotypes. 41 The clinical implications of this have not been adequately studied but it would seem that the RM and EM phenotypes would have less analgesia. 42 Tramadol, like codeine, is a prodrug that requires conversion to its active metabolite and thus also subject to variable metabolism; ultra-rapid metabolism has resulted in at least one fatality.…”
Section: Polymorphisms and Risk For Respiratory Depressionmentioning
confidence: 99%